PERANCANGAN SISTEM INFORMASI PENCATATAN GUDANG BERBASIS WEBSITE (STUDI KASUS SLINGBAG SALATIGA) - Hansel Yonathan Senduk; Melkior N N Sitokdana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The development of Information Technology and Information Systems at this time is very rapid so that business activities apply technology in it. Slingbag Salatiga is a shop that sells bags and several products with various variants. However, in its business activities, Slingbag Salatiga still has not implemented information system technology in it, especially in recording incoming goods from suppliers to warehouses, from warehouses to stores, causing an impact, namely errors in data input and differences in stock between goods from warehouse to store. In this study, designing a-based warehouse recording information system website which is expected to make it easier for admins to record incoming and outgoing goods properly. In designing this system using the SDLC (methodSystem Development Life Cycle)which at this stage starts from needs analysis, design, implementation, testing to maintenance. On website this, there is a function of entering goods that enter the warehouse from the supplier to the goods leaving the warehouse to the store where there is clear information and validation so as to reduce the risk of fraud or manipulation of thedata of the stock goods sent.